Intersectional analysis of walkability in Belo Horizonte from a racial and gender perspective - Alves, Alícya David Ferreira; Mülfarth , Roberta Consentino Kronka (Technical and Scientific Journal Green Cities, 2025)
Objective – The study aims to assess walkability in the planned area of ​​Belo Horizonte, comparing the application of the Ergonomic Pedestrian Comfort Index (ICEP), developed by Albala (2022), with popular perceptions obtained through a questionnaire. Additionally, a micro-scale study is conducted on the block where part of the author’s family lived, incorporating a memory dimension into the urban analysis. The article also incorporates gender and race perspectives, highlighting how these markers influence the walking experience and challenge the limits of strictly technical assessments. The specific objectives are: Apply the ICEP in the planned area of ​​Belo Horizonte using urban databases; Develop and administer an online questionnaire to collect popular perceptions of walkability, considering sociodemographic variables; Critically analyze the indices for the absence of indicators related to gender and race; Critically compare the results of the two indices used, highlighting the differences between popular perception and technical research; Conduct a micro-scale study of the block where the researcher’s family lived, comparing old and current photographs; Integrate the family narrative as an illustrative element of the dynamics of urban exclusion in Belo Horizonte; Reinforce the understanding and importance of walking as a priority mode of transport in decision-making on public urban mobility policies; Contribute guidelines, at the urban design level, based on the revision of the Belo Horizonte Master Plan. Methodology – The manuscript was written using a qualitative and quantitative approach, combining technical methods of spatial analysis with instruments for investigating subjective perception, to understand the walkability conditions in the planned area of ​​Belo Horizonte and their relationship with social markers of gender and race. The first stage consisted of surveying and systematizing literature on walkability, the right to the city, race, gender, and urban planning. Based on this framework, a set of methodological procedures was defined for analyzing walkability in the internal area of ​​Avenida do Contorno, the core of the original project for the capital of Minas Gerais. The second stage involved applying the Ergonomic Pedestrian Comfort Index (ICEP), developed by Albala (2022), with adaptations for the study area. Subsequently, the research continued with the development and administration of a structured questionnaire aimed at visitors and residents of the central and south-central regions. The instrument was constructed based on 27 walkability indicators formulated by Carvalho (2018), organized as statements on a Likert scale. The questions sought to capture participants’ perceptions of the comfort, safety, attractiveness, and accessibility of spaces, as well as sociodemographic factors, enabling intersectional analyses. This data collection was complemented by open-ended interviews with two women who lived in the planned area of ​​Belo Horizonte before being relocated to peripheral areas. The analysis of these narratives was interconnected with a spatial reading of the original block where they lived, supported by historical and current images collected during field visits. The study progressed with a comparative analysis of ICEP data and the perceptions collected via questionnaire. This comparison allowed us to observe convergences and divergences between the technical reading, popular perception, and the analysis of memories of walkability, with a focus on the intersections of race and gender. Data triangulation revealed elements not captured by conventional indicators, reinforcing the importance of approaches sensitive to urban inequality. Originality/Relevance – The article integrates urban infrastructure, social perceptions, and intersectional perspectives of gender, race, and territorial affiliation in assessing walkability—dimensions rarely considered in traditional methodologies. It contributes to the debate on the right to the city and urban and territorial justice, based on a critical approach that combines technical elements and everyday experience, broadening the understanding of urban mobility and guiding equitable policies. Results – From a technical perspective, the application of the ICEP resulted in mild discomfort, but with a spatial contrast. However, popular perception, as elicited by the questionnaire, revealed a more critical result, especially among women and Black people, who associated insecurity with poor lighting and the absence of people on the streets. Comparing the two results demonstrates the limitations of strictly technical assessments, which tend to obscure social and identity inequalities. The study of Curvelo Street, in turn, reinforced this framework by highlighting how processes of racial segregation and rising real estate values ​​transformed the space. Theoretical/Methodological Contributions – The study clarifies that walkability cannot be understood solely through technical indicators or from a neutral and universal perspective; it is essential to incorporate social perceptions and intersectional perspectives. Theoretically, it highlights walking as a social and political practice, reinforcing the need for urban policies and assessments that consider subjective experiences. Methodologically, the integration of ICEP, a popular questionnaire, and a microscale study allows for the identification of gaps in traditional instruments. Social and Environmental Contributions – The article highlights that walkability is not limited to infrastructure, implying issues of urban justice and the right to the city. Methodological integration highlights gaps in technical indicators and persistent inequalities. In this context, environmental elements, such as trees, shade, and sidewalk continuity, impact comfort and safety, indicating that urban policies must combine infrastructure, social equity, and environmental quality to promote more just and sustainable cities.